The Characteristics of Clinical Studies Submitted to the Saudi Food and Drug Authority from 2009 until 2020 - Mohammad H. Aljawadi; Renad A. Aldhahri; Mansour S. AlMetwazi; Azher Arafah; Abdullah T. Khoja (Elsevier, 2021)
Background: Clinical trials are crucial in contemporary evidence-based medicine for discovering new treatments for diseases. Their registration in a registry increases the transparency in the dissemination of knowledge about clinical research. It is essential to understand the activity of clinical trials in a country, thus identifying research gaps. Objective: This study, therefore, aims to describe the clinical trial activity since the inception of clinical trials' administration and national clinical trials' registry within the Kingdom of Saudi Arabia (KSA). Method: A descriptive study was conducted by reviewing all clinical studies that have been registered during 2009 and June 2020. The inclusion criterion was all phases of the clinical trials registered in the national registry during that period. Data analysis was done using descriptive statistics. Results: Since 2009, 352 studies have been registered. However, a total of 333 studies with complete data was included in the analysis. A total of 80 sponsors funded the clinical studies in the KSA. The majority of the clinical studies are funded by multinational pharmaceutical companies. Oncology (13.81%) and diabetes (11.71%) were the most common therapeutic areas and constituted the largest proportion of the overall studies. 44% were phase 4 and 40% were phase 3 studies. Conclusion: With a population approaching 34 million, the number of clinical trials in the KSA is not sufficient. Since the inception of the clinical trial's administration and SCTR, the emphasis has been on phase 3 and phase 4 clinical studies. The most studied therapeutic areas were oncology and diabetes. Many clinical studies in the KSA were sponsored by multinational pharmaceutical companies.